Capillary water absorption in mixtures of cohesive soils stabilized with cement and hydrophobic agent - Węgliński, Szymon (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
The paper presents the results of tests on capillary water absorption of mixtures from cohesive soils - clayey sand and sandy clay - stabilized with cement and the addition of a hydrophobic binder. Studies have shown that the appropriate addition of diamidoamine lactate allows to limit the penetration of water inside the stabilized samples, which increases their frost resistance. The mixtures with the additive showed lower capillary water absorption compared to the mixtures stabilized only with cement, especially in the first few hours after soaking with water.